Perancangan Ulang Tata Letak Fasilitas pada Industri Garmen dengan Metode BLOCPLAN - Santoso, Santoso; Heryanto, Rainisa Maini; Kartawidjaja, Maria Angela; Sukwadi, Ronald (Universitas Teuku Umar, 2024)
Currently, developments and changes are occurring very rapidly in the garment industry. Technological advances and the recent Covid-2019 pandemic have led to a significant increase in online product purchases. This has had quite a big impact, as the movement of materials within the industry can change significantly. Such changes can render material movement less efficient, leading to a decrease in work productivity. Therefore, it is necessary to redesign the layout to ensure efficient material movement. The goal of this layout redesign is to minimize the total distance moved. Computer-aided layout (CAL) has garnered much interest from researchers, as it offers benefits such as generating numerous alternative layout improvements in a short time. The method used for redesigning the layout in this research is one CAL method, namely the Block Layout Overview with Layout Planning (BLOCPLAN) method. In this case study, data processing will be carried out using BLOCPLAN-90 software. The total material movement distance in the initial layout is 119,885.25 meters per month, while the total distance of material movement in the proposed layout is 61,840.33 meters per month. This indicates a decrease in the total material movement distance of 58,044.92 meters per month, or a reduction of 48.42 percent. With a decrease in the total material movement distance, it is expected that work efficiency and productivity will increase.